2020
DOI: 10.1016/j.jss.2019.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Interruptions in Surgery: A Comprehensive Review

Abstract: Background: Recent literature showed that analysis of interruptions can contribute to evaluating the care process in the operating room and thus understanding potential errors which may occur during surgical procedures. The aim of this comprehensive review was to summarize current knowledge on the description and impact of interruptions in surgery. Material and methods: A literature search was conducted according to a set of criteria in the databases MEDLINE, BASE, Cochrane's Library and PsycINFO. Results: 41 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 63 publications
(72 reference statements)
1
14
0
7
Order By: Relevance
“…The definition of each type of FD can be found in Table 1. All FDs were further classified for severity of FD based on a taxonomy developed by Parker et al [21]. Flow disruptions were classified into one of six categories: 1-no impact/minor disruptionno response; 2-momentary disruption (acknowledgement of disruption, no pause in task); 3-momentary distraction (short pause < 10 s); 4-primary task interrupted (task cessation > 10 s); 5-primary task disruption (secondary task engaged); 6-repeat task.…”
Section: Flow Disruptionsmentioning
confidence: 99%
“…The definition of each type of FD can be found in Table 1. All FDs were further classified for severity of FD based on a taxonomy developed by Parker et al [21]. Flow disruptions were classified into one of six categories: 1-no impact/minor disruptionno response; 2-momentary disruption (acknowledgement of disruption, no pause in task); 3-momentary distraction (short pause < 10 s); 4-primary task interrupted (task cessation > 10 s); 5-primary task disruption (secondary task engaged); 6-repeat task.…”
Section: Flow Disruptionsmentioning
confidence: 99%
“…The actual effects of FDs on the surgery itself, on providers and patient care are manifold. 11 Previous investigations found that FDs lead to higher stress levels, fatigue 12 and expand Systematic review procedure time, for example, in cardiac surgery, about 7% of operating time was associated with FD events. 13 Other studies reported larger delays up to 20%.…”
Section: Introductionmentioning
confidence: 97%
“…16 As current research suggests that different types of FDs may have specific effects-some are harmful, others beneficial and some essential for a seamless surgical workflowdetailed classification and systematic aggregation is essential. 11 Despite the growing interest and literature on surgical FDs, there is, to the best of our knowledge, no systematic review that synthesises the current research base and considers the diversity of potential effects. In contrast to previous reviews, 6 11 our review further sought to encompass the broad spectrum of potential consequences as well as to systematically appraise the methodological quality of the study base.…”
Section: Introductionmentioning
confidence: 99%
“…Any additional stress factors potentially increases this risk for patient's safety and outcomes [3,4]. One of these challenges are flow disruption events (FDs) which have been found to be ubiquitous in the OR [5,6]. FD incidents have been described as 'deviations of the natural progression of the operative procedure' [7,8].…”
Section: Introductionmentioning
confidence: 99%